2004
DOI: 10.1203/01.pdr.0000099774.17723.d4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Brain Levels of F2-Isoprostane Are an Early Marker of Behavioral Sequels in a Rat Model of Global Perinatal Asphyxia

Abstract: Perinatal asphyxia is a major cause of immediate and postponed brain damage in the newborn. It may be responsible for several delayed neurologic disorders and, in this respect, early markers of brain injury would be relevant for therapeutic intervention as well as for identification of infants at high risk for developmental disabilities. Biochemical measurements (brain F 2 -isoprostane levels) and behavioral tests (ultrasonic vocalization pattern on postnatal days (pnd) 5, 8, and 11, spontaneous motor behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
(45 reference statements)
4
14
0
Order By: Relevance
“…The finding that early environmental factors can influence calling behavior is in accordance with studies on the effects of prenatal malnutrition (Tonkiss et al 2003), prenatal stress (Morgan et al 1999;Williams et al 1998), perinatal asphyxia (Calmandrei et al 2004) or pre-and postnatal exposure of various substances, like alcohol (Barron and Gilbertson 2005;Marino et al 2002;Tatolli et al 2001), cocaine (Hahn et al 2000), lead (De Marco et al 2005), aluminum (Alleva et al 1998), or carbon monoxide (Di Giovanni et al 1993) on ultrasonic calling in infant rodents. However, in the natural context, variations in maternal care might be of major importance.…”
Section: Within-strain Embryo-transfer: Comparison Between B6jola Andsupporting
confidence: 84%
“…The finding that early environmental factors can influence calling behavior is in accordance with studies on the effects of prenatal malnutrition (Tonkiss et al 2003), prenatal stress (Morgan et al 1999;Williams et al 1998), perinatal asphyxia (Calmandrei et al 2004) or pre-and postnatal exposure of various substances, like alcohol (Barron and Gilbertson 2005;Marino et al 2002;Tatolli et al 2001), cocaine (Hahn et al 2000), lead (De Marco et al 2005), aluminum (Alleva et al 1998), or carbon monoxide (Di Giovanni et al 1993) on ultrasonic calling in infant rodents. However, in the natural context, variations in maternal care might be of major importance.…”
Section: Within-strain Embryo-transfer: Comparison Between B6jola Andsupporting
confidence: 84%
“…However, directly after PA, when the foetal circulation and metabolism is still maintained, there were no apparent changes in the activity or transcription of nNOS (Lubec et al 1999) or inducible NOS (Calamandrei et al 2004). Early intervention in NO production could have long-term therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, increased brain levels of 8-epi-PGF2a were found in asphyctic newborn rats 2 h after global perinatal asphyxia, and this biomarker could be predictive of delayed behavioral disturbances [22]. These biomarkers have several advantages, such as establishing a quantitative result and diagnosis to clinically undefined samples, and being potential long-term neurological damage biomarkers [14,22]. This fact can be explained by the molecular damage occurred under hypoxic episode depending on its intensity, duration, previous metabolic state, gestational age, and the degree of development of the antioxidant system, altogether these factors can induce a different response to a hypoxic episode.…”
Section: Compoundsmentioning
confidence: 98%
“…When comparing cord serum samples, we found that 8-iso-15(R)-PGF2α and total isoprostanes had a highly significant correlation with severe postnatal metabolic acidosis. Actually, increased brain levels of 8-epi-PGF2a were found in asphyctic newborn rats 2 h after global perinatal asphyxia, and this biomarker could be predictive of delayed behavioral disturbances [22]. These biomarkers have several advantages, such as establishing a quantitative result and diagnosis to clinically undefined samples, and being potential long-term neurological damage biomarkers [14,22].…”
Section: Compoundsmentioning
confidence: 99%